Enhanced Integration of Newborn Neurons after Neonatal Insults - Pugh, Phyllis C.; Adlaf, Elena W.; Zhao, Chaunsheng; Markwardt, Sean J.; Gavin, Cristin F.; Wadiche, Jacques I.; Overstreet-Wadiche, Linda (Frontiers in Neuroscience, 2011)
The production and integration of adult-generated neurons in the dentate gyrus is dramatically perturbed by a variety of pathological insults, including repetitive seizures and hypoxia/ischemia. Less is known about how insults affect early postnatal neurogenesis, during the developmental period when the majority of dentate neurons are produced. Here we tested how single episodes of hypoxia or chemically-induced seizure activity in postnatal day 10 mice alter granule cell production and integration. Although neither insult was sufficient to alter the number of newborn neurons nor the population of proliferating cells, both treatments increased the dendritic complexity of newborn granule cells that were born around the time of the insult. Surprisingly, only the dendritic enhancement caused by hypoxia was associated with increased synaptic integration. These results suggest that alterations in dendritic integration can be dissociated from altered neural production and that integration appears to have a lower threshold for perturbation. Furthermore, newborn neurons in adult mice that experienced neonatal hypoxia had reduced dendritic length while having no alterations in number. Together these results suggest that single insults during the neonatal period can have both long- and short-term consequences for neuronal maturation.